Safar āshnā - Narang, Gopi Chand, 1931- (Ejūkeshnal Pablishing Hāʼūs, 1982)
Travel impressions of Europe, Canada, United States of America, etc., of an Urdu scholar; with special mention of the literary activities of Urdu poets and authors living in foreign countries.